Micro Teaching as Efficient Technique to Increase Self-Efficacy of Prospective Biology Teacher: Evidence from First Year Teacher - Marlina*, Reni; Suwono, Hadi; Yuenyong, Chokchai; Ibrohim, Ibrohim; Pamungkas, Rahmania; Hamdani, Hamdani (Jurnal Pendidikan Sains Indonesia, 2024)
This study focuses on the perspective of prospective teachers on the development of self-efficacy during teaching practice in micro teaching and also during real teaching. The problem in this study is what factors influence the development of self-efficacy during micro teaching and real teaching? The purpose of this study is to describe the factors that contribute to the development of self-efficacy during micro teaching and real teaching. This study uses a descriptive qualitative method. The participants of the study were first-year biology teachers who had taken micro teaching courses at college. The instruments used included questionnaires and interview sheets. The results obtained were that during micro teaching, prospective teachers had high self-efficacy in three factors, namely performance experience, other people's experiences, and social support. Meanwhile, after teaching at school (real teaching), the factors that support the development of self-efficacy are physiological and emotional states. In order for self-efficacy to develop well during real teaching, it can be concluded that micro teaching is an efficient technique in improving the self-efficacy of prospective biology teachers. It is necessary to form a learning community in schools that can be used as a forum for teachers to collaborate with each other in finding efficient strategies in teaching. This can support the development of teacher self-efficacy.